Labour contract regulations and workers' wellbeing: international longitudinal evidence - Andrea Salvatori (Institute for the Study of Labor (IZA), 2010)
All industrialized countries have Employment Protection Legislation (EPL) for permanent workers and Restrictions on the use of Temporary Employment (RTE). The (ambiguous) effects of these on the levels of employment and unemployment have been extensively studied, but nothing is known empirically about their well-being implications. Using longitudinal data from the European Community Household Panel, the author conducts the first study of the link between both EPL and RTE and workers' wellbeing. The results provide evidence that both permanent and temporary employees gain from reforms that ease restrictions on temporary employment but leave firing costs for permanent workers unchanged. This finding contrasts with common claims found in the political economy literature.
Keywords: J28; 330; Temporary employment; employment protection legislation; job satisfaction; Arbeitnehmerschutz; Befristeter Arbeitsvertrag; Arbeitsrecht; Arbeitszufriedenheit; EU-Staaten